Argentophilic pyridinic nitrogen for embedding lithiophilic silver nanoparticles in a three-dimensional carbon scaffold for reversible lithium plating/stripping. Issue 4 (4th January 2022) - Jeon, Yuju; Kim, Jonghak; Jang, Haeseong; Lee, Jeongin; Kim, Min Gyu; Liu, Nian; Song, Hyun-Kon
Abstract : Ten times heavy silver loading into a 3D scaffold via a strong Ag + –pN interaction between silver cations and argentophilic pyridinic nitrogen of melamine provides a strong lithiophilicity, largely improving lithium plating/stripping reversibility. Abstract : Reversible lithium metal plating and stripping are required for the durable operation of lithium metal batteries. Three-dimensional architecture has been employed for accommodating volume change of lithium metal during repeated plating and stripping while lithiophilic materials have been utilized for the even plating of lithium metal. One of the best pictures would be a three-dimensional electrically conductive scaffold having a significant amount of lithiophilic sites homogenously distributed on its skeleton. To realize the ideal architecture for lithium metal anodes, herein, we embedded silver nanoparticles as lithiophile in a three-dimensional carbon scaffold. To overcome the limited loading amount of silver in the porous structure, melamine as an argentophile having argentophilic (silver-philic) pyridinic nitrogen was introduced into the carbon scaffold. Melamine as the argentophile increased the silver loading ten times in the three-dimensional scaffold via the strong interaction with silver cation. The heavy lithiophile (silver) loading increased the lithium storage capacity, guaranteeing uniform lithium distribution throughout the scaffold. The silver nanoparticles loaded in the scaffold were alloyed with lithium to be silver–lithium alloy (Ag x Li y ) during lithium metal plating. The alloy served as the lithiophilic nucleation sites for the dendrite-free growth of lithium metal. As a result, the strong lithiophilicity derived from the heavy-loading silver improved the reversibility of lithium plating and stripping. The cycling durability of lithium metal batteries with lithium-ion-battery cathode reaction and oxygen reduction reaction was twice improved by employing the lithium-metal-infused 3D scaffold anode having the highest lithiophile loading with internal space enough to accommodate the volume of lithium metal.